FILOSOFI AKAD WADIAH DI LEMBAGA KEUANGAN SYARIAH - Na'im, Fairuz 'Ainun (Insitut Pesantren Babakan cirebon, 2023)
AbstractThis article is written to analyze the theory surrounding and practice of wadiah and its philosophical views from both classical and contemporary scholars. The research in this article uses a qualitative method with a literature research approach that explores the theoretical and philosophical sides of various authoritative sources on wadiah. The results show that in wadiah there are philosophical aspects resulting from the maqashid perspective in viewing wadiah as an instrument in the maintenance of assets (hifdh al-mal) to the development of Islamic economics in general. This article is expected to be a philosophical foundation for those who research contracts in Islamic economics in general and wadiah in particular, and useful for further research in the field of Islamic economic legal philosophy.Keywords: philosophy, wadiah, LKS